Além do que se vê : educação crítica e letramentos, formação de professores e prática docente no ensino de inglês com crianças de 2 a 5 anos - Malta, Liliane Salera (2019)
This qualitative interpretative research with autoetnographic characteristics aims to understand how English teachers for children from 2 to 5 years-old dialogue with Critical Education and Critical Literacies – especially Visual Literacies and Multiliteracies – in a context of continuous education, exploring the mediation between theory and practice in the English teaching for Early Childhood Education, helping us to understand our educational praxis. In addition, this research is justified not only by the notable expansion of the English learning scenario for children, but also by its contribution to teacher education and to the teaching-learning process. Thus, we created a teacher education course focused on discussions related to Critical Education and Literacies, encompassing both theories and teaching practices with this vision, which led us to reflections (personal and related to the group) explored in the theoretical-analytical chapters of this research. Finally, we understand that the course was valid not only for our education as educators – and this author’s education as a teacher trainer – but for the creation of a support network with professionals working in similar contexts that felt sheltered when discussing challenges common to all.